Podnikatelský záměr - nákup moderní technologie - Musil, Jiří (Vysoké učení technické v Brně. Fakulta podnikatelská, 2012)
Práce se zaměřuje na možnosti pořízení moderní technologie s důrazem na příležitost využití grantu z fondů EU. Záměrem je postihnout teoretické předpoklady a analýzu situace firmy. Výstupem má být projekt, který předpokládá udělení dotace.

The diploma thesis focuses on the acquisition of modern technology with an emphasis on the opportunity to use grant funds from the EU. The intention is to capture the assumptions and theoretical analysis of the situation of the company. The result should be a project which envisages the granting of subsidies.
Business Plan - Purchase of Modern Technology
Keywords: Dotace z EU; projekt; Rozvoj; fondy Evropské unie; výrobní technologie; financování.; EU subsidies; project; development; European Union fund; manufacturing technology; financing.